Turkey's presidential system after two and a half years: An overview of institutions and politics - Sinem Adar; Günter Seufert (Stiftung Wissenschaft und Politik (SWP), 2021)
Turkey's new Presidential System has failed to realise the goals that it was said to achieve with its introduction despite the disapproval of half the population. Contrary to the ruling party's claims in favour of the new governance system, two and a half years after its introduction, parliament is weaker, separation of powers is undermined, the judiciary is politicised, institutions are crippled, economic woes are mounting and authoritarian practices prevail. Despite the almost unlimited and unchecked power that the new system grants to the President over institutions, his space for political manoeuvre is, surprisingly, narrower than it was in the parliamentary system. Providing the otherwise divided opposition a joint anchor of resistance, the Presidential System unintentionally breathed life into the inertia of Turkey's political party setting. The formation of splinter parties from the ruling party, primarily addressing the same conservative electorate, alongside the changing electoral logic with the need to form alliances to win an election, poses a serious challenge to the ruling party and its leader - the President. Despite the oppositional alliance's electoral victory in 2019 local elections, it is at the moment unclear whether the forming parties share a common vision for steps towards democratic repair. Together with the institutional havoc caused by the Presidential System, the blurry outlook of the opposition requires caution about an easy and rapid positive transformation. While the European Union should be realistic in regard to expectations towards democratic reform, it should also strike a balance between cooperation in areas of mutual benefit and confronting Ankara when necessary to protect the interests of the European Union and its member states.
Keywords: 320; Bilateral international relations